Macrovascular Complications of Type 2 Diabetes Mellitus - Viigimaa, Margus; Sachinidis, Alexandros; Toumpourleka, Maria; Koutsampasopoulos, Konstantinos; Alliksoo, Signe; Titma, Tiina (Current Vascular Pharmacology, 2020)
Background: Type 2 diabetes mellitus (T2DM) has emerged as a pandemic. It has different complications, both microvascular and macrovascular. Objective: The purpose of this review is to summarize the different types of macrovascular complications associated with T2DM. Methods: A comprehensive review of the literature was performed to identify clinical studies, which determine the macrovascular complications associated with T2DM. Results: Macrovascular complications of T2DM include coronary heart disease, cardiomyopathy, arrhythmias and sudden death, cerebrovascular disease and peripheral artery disease. Cardiovascular disease is the primary cause of death in diabetic patients. Many clinical studies have shown a connection between T2DM and vascular disease, but almost always other risk factors are present in diabetic patients, such as hypertension, obesity and dyslipidaemia. Conclusion: T2DM causes a variety of macrovascular complications through different pathogenetic pathways that include hyperglycaemia and insulin resistance. The association between T2DM and cardiovascular disease is clear, but we need more clinical studies in order to identify the pure effect of T2DM.
Keywords: hyperglycaemia